2019
DOI: 10.7126/cumudj.492598
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Pain During Glide Path Creation with the Use of a Rotary or Reciprocating System

Abstract: Objectives: The objective of this study was to compare the intraoperative pain levels of patients caused from using different glide path systems in creating the glide path before the root canal shaping the teeth with asymptomatic irreversible pulpitis. Materials and Methods: The study included 88 patient with asymptomatic irreversible pulpitis in mandibular molar tooth. The teeth were randomly assigned to four groups according to use of glide path files: R-pilot (RP), WaveOne Gold Glider (WOG G), One G (OG), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Instrumental techniques used in the treatment and preparation of root canals for threedimensional homogeneous obturation may play a role in the development of postoperative pain, as necrotic pulp particles, contaminated dentinal sawdust and bacteria can invade the periapical region, causing an inflammatory response. All instrumentation methods are associated with the extrusion of in-canal content, and its amount varies depending on the kinematics and design of the tool used [7,8,13,22]. According to the authors, the use of the "glide path" method (mainly rotary instruments) at the initial stages of root canal preparation can reduce the amount of substances extruded behind the apex, which, in turn, reduces the response from the periapical tissues, reducing postoperative sensitivity and pain, since there is no massive release of chemical mediators of inflammation, such as neuropeptides, metabolites of arachidonic acid, cytokines, lysosomal enzymes, platelet activating factor, fibrinolytic peptides, vasoactive amines, kinins and others [1].…”
Section: Apical Extrusion Of Intracanal Content Postendodontic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrumental techniques used in the treatment and preparation of root canals for threedimensional homogeneous obturation may play a role in the development of postoperative pain, as necrotic pulp particles, contaminated dentinal sawdust and bacteria can invade the periapical region, causing an inflammatory response. All instrumentation methods are associated with the extrusion of in-canal content, and its amount varies depending on the kinematics and design of the tool used [7,8,13,22]. According to the authors, the use of the "glide path" method (mainly rotary instruments) at the initial stages of root canal preparation can reduce the amount of substances extruded behind the apex, which, in turn, reduces the response from the periapical tissues, reducing postoperative sensitivity and pain, since there is no massive release of chemical mediators of inflammation, such as neuropeptides, metabolites of arachidonic acid, cytokines, lysosomal enzymes, platelet activating factor, fibrinolytic peptides, vasoactive amines, kinins and others [1].…”
Section: Apical Extrusion Of Intracanal Content Postendodontic Painmentioning
confidence: 99%
“…The design features and taper of the One G file also help remove debris more efficiently than K-files, as do the ScoutRace, R-pilot and WaveOne Gold Glide [3,13].…”
Section: Apical Extrusion Of Intracanal Content Postendodontic Painmentioning
confidence: 99%
“…The references of the six studies were carefully assessed to identify studies retrieved through the main search strategy, but none were found. Therefore, the six studies [2,4,18,[32][33][34] were included in the qualitative analysis of the results. Figure 1 shows the search, identification, inclusion, and exclusion processes for the articles.…”
Section: Study Selectionmentioning
confidence: 99%
“…The analysis of the six studies resulted in a total sample of 884 patients/ teeth, whose ages ranged from 16 to 70 years. From the six studies analyzed, only three [2,4,34] mentioned the ethical criteria involved, three [2,4,34] followed the CONSORT statement, and two reported the use of informed consent forms for the research participants [4,34]. Table 3 shows a summary of the main intervention characteristics of the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation